Factors Affecting Students' Statistical Literacy Ability in Indonesia (Meta-Analysis) - Khairunnisa; Nurul Astuty Yensy (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Statistical literacy is an important skill needed by students to understand data and make decisions based on accurate information. This study uses meta-analysis to identify the factors influencing students' statistical literacy skills in Indonesia. Data were collected from 19 studies conducted between 2017 and 2024. The research results indicate that the learning model, major, and school quality play important roles. In addition, internal factors such as learning styles, statistical anxiety, and levels of mathematical thinking are also very influential. These findings are expected to assist teachers and policymakers in designing more effective learning strategies to enhance statistical literacy skills in the future.